Relationship Between Participation in Maternity Classes and Knowledge About Pregnancy and Childbirth - Febrianti; Christin Angelina F; Dhiny Easter Yanti; Nurhalina Sari (Postgraduate, University of Mataram, 2023)
The participation of pregnant women in pregnant women's classes increases mothers' knowledge about the danger signs of pregnancy. Classes for pregnant women at the Krui Health Center run according to a predetermined schedule. However, after evaluating the K4 visit, it was found that the K4 achievement was still below the target of 95%. This study aimed to determine the relationship between maternal participation in pregnant women classes and knowledge about pregnancy and childbirth in the Working Area of ​​the Krui Health Center, Pesisir Barat Regency, in 2023. This type of research is quantitative with a cross-sectional design. The population in this study were all third-trimester pregnant women with gestational age > 36 weeks in the Working Area of ​​the Krui Health Center with a total of 51 people. The sampling technique used is total sampling. Data collection instruments used questionnaires and the MCH book. Data analysis in this study used univariate and bivariate (chi-square). The results of this study indicate that 29 (56.9%) respondents actively attended classes for pregnant women, and 28 (54.9%) respondents had good knowledge. The data analysis results show a relationship between mothers' participation in pregnant women's classes and learning about pregnancy and childbirth in the Working Area of ​​the Krui Health Center, Pesisir Barat Regency, in 2023, with a p-value of 0.042. Pregnant women are expected to actively participate in classes for pregnant women to increase their knowledge about matters in pregnancy and childbirth.